Endothelial-to-mesenchymal transition: Cytokine-mediated pathways that determine endothelial fibrosis under inflammatory conditions. (February 2017) - Pérez, Lorena; Muñoz-Durango, Natalia; Riedel, Claudia A.; Echeverría, Cesar; Kalergis, Alexis M.; Cabello-Verrugio, Claudio; Simon, Felipe
Graphical abstract: Highlights: Endothelial fibrosis mediated by endothelial-to-mesenchymal transition (EndMT) has been involved in inflammatory diseases. TNF-α, IL and TGF-β induce EndMT-mediated endothelial fibrosis. Oxidative stress and bacterial toxins triggers EndMT-mediated endothelial fibrosis through a mechanism mediated by TGF-β/ALK5/smad pathway. Abstract: During the last decade, the endothelial-to-mesenchymal transition (EndMT) process has attracted considerable attention due to associations with the onset of certain diseases, such as organ fibrosis and cancer. Several studies have assessed the mechanisms and signaling pathways that regulate endothelial fibrosis in the context of human pathologies. A number of inflammatory mediators, including pro-inflammatory cytokines, growth factors, oxidative stress, and toxins, induce the conversion of endothelial cells into mesenchymal fibroblast-like cells that promote disease progression. This review is separated into five chapters that critically present current knowledge on EndMT in the context of pathology. First, the main characteristics of EndMT are summarized, with a focus on the endothelial protein pattern changes that modulate the expressions of endothelial/fibrotic markers and extracellular matrix proteins. These expressions could serve as mechanisms for explaining potential EndMT contributions to human pathologies in adults. Second, the main findings supporting a connection between EndMT-mediated endothelial fibrosis and inflammatory conditions are presented. These connections could be linked to the onset and progression of pathological conditions. Third, EndMT inducers are described in detail. This includes considerations on the actions of the first and most well-known EndMT inducer, TGF-β; of the most prominent pro-inflammatory cytokines released during inflammation, such as IL 1-β and TNF-α; and of the NF-κB transcription factor, a common player during inflammation-induced EndMT. Furthermore, thorough attention is given to EndMT induction by endotoxins in the context of bacterial infectious diseases. Additionally, the participation of the inflammatory oxidative stress environment in the EndMT induction was also reviewed. Fourth, the pathophysiological findings of inflammation-induced EndMT are presented, and, fifth, special focus is placed on associations with cancer onset and development. Altogether, this review highlights the important role of EndMT-mediated endothelial fibrosis during inflammation in human pathologies.